Dynamics of small genetic circuits subject to stochastic partitioning in cell division - Lloyd-Price, Jason; Tran, Huy; Ribeiro, Andre S. (Journal of theoretical biology, 2014)
In prokaryotes, partitioning errors during cell division are expected to be a non-negligible source of cell-to-cell diversity in protein numbers. Here, we make use of stochastic simulations to investigate how different degrees of partitioning errors in division affect the cell-to-cell diversity of the dynamics of two genetic circuits, a bistable switch and a clock. First, we find that on average, the stability of the switch decreases with increasing partitioning errors. Despite this, anti-correlations between sister cells, introduced by the partitioning errors, enhance the chances that one of them will remain in the mother cell׳s state in the next generation, even if the switch is unstable. This reduces the variance of the proportion of phenotypes across generations. In the genetic clock, we find that the robustness of the period decreases with increasing partitioning errors. Nevertheless, the population synchrony is remarkably robust to most errors, only significantly decreasing for the most extreme degree of errors. We conclude that errors in partitioning affect the dynamics of genetic circuits, but the effects are network-dependent and qualitatively different from noise in gene expression. •We study effects of partitioning errors on the dynamics of genetic circuits.•Effects of partitioning errors differ widely with network topology and behavior.•In switches, errors reduce the phenotype distribution׳s variance across generations.•The synchrony of a population with clocks is robust to the majority of errors.•Errors produce qualitatively different effects than noise in gene expression.